The Role of Benefits and Convenience on Consumer Interest in Online Transactions in Bukalapak - Wanda Gema Prasadio Akbar Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to investigate how perks and convenience affect consumers' intentions to continue doing business online. Students from several Surabaya tertiary universities who used the Buka Bukalapak website to conduct online transactions made up the research respondents. Multiple regression analysis is utilized to evaluate the presented hypothesis, with benefits and convenience acting as independent variables and interest in continuing online transactions acting as a dependent variable. The findings demonstrated that the advantages and ease had a notable favorable impact on the desire to continue online transactions on the Buka Bukalapak website. This demonstrates that the greater the benefits of conducting business on the Bukalapak website and the greater the consumer's comfort level with conducting business on the Bukalapak website, the greater the consumer's interest in conducting business again